MUTATION OF LIPASE-PRODUCING BACTERIAL ISOLATE FROM PALM OIL EFFLUENT FOR FAT HYDROLYSIS ON POME - dadang suhendar; Ika Rahmatul Layly; Gabriela Christy Sabbathini; Deden Rosid Waltam; Edi Wahjono; Catur Sriherwanto; Haniyya Haniyya (Jurnal Bioteknologi dan Biosains Indonesia, 2023)
Lipase is applied to hydrolyzethe residual oil or fat in palm oil mill effluent (POME), which serves as a feedstock for biogas production. A bacterial isolate (Bacillus velezensis) exhibiting lipase activity, previously obtained from Malimping, Pandeglang, Banten, Indonesia, underwentsequential treatments of gamma irradiation (1, 2, and 3 kGy), EMS (ethyl methane sulfonate) mutagenesis (0.5% v/v), and NTG (N-methyl N-nitrosoguanidine) (1 mg mL-1). Following each mutation, lipase activities of the mutant colonies were measured and compared to the wild-type strain. The results revealed that all mutated B. velezensiscolonies exhibited lipase activity values (7.78 ± 0.80 –9.05 ± 0.23 U mL-1) that were not significantly different from the wild-type isolate (8.31 ± 0.01 U mL-1), indicating strong bacterial resistance against the mutagenic treatments. The crude lipase preparation effectively hydrolyzed POME, resulting in a reduction of the COD value (from 131,450 ppm to 88,450 ppm) and O&G content (from 41,400 mg L-1to 5,770 mg L-1) within a 72-hour timeframe.